On Certain Inequalities for Several Kinds of Strongly Convex Functions for q-h-Integrals - Ghulam Farid; Wajida Akram; Ferdous M. O. Tawfiq; Jong-Suk Ro; Fairouz Tchier; Saira Zainab (Fractal and Fractional, 2023)
This article investigates inequalities for certain types of strongly convex functions by applying q-h-integrals. These inequalities provide the refinements of some well-known results that hold for <semantics>(α,m)</semantics>- and <semantics>(ℏ</semantics>-<semantics>m)</semantics>-convex and related functions. Inequalities for q-integrals are deducible by vanishing the parameter h. Some particular cases are discussed after proving the main results.